Multiple comparisons - Klockars, Alan J. (Sage University papers / Quantitative applications in the social sciences)
1. Multiple comparisons -- The example -- The null hypothesis -- Variance estimates or mean squares -- The F-ratio -- Decision rules and statistical significance -- Decision errors -- Selecting the most appropriate multiple-comparison test -- Selecting a multiple-comparison test and Type I errors -- Definitions and meanings of Type I errors in multiple-comparison tests -- Types of multiple comparisons -- Test statistics -- 2. Priori comparisons -- Orthogonal comparisons -- Characteristics of orthogonal comparisons -- Decision rule for evaluating orthogonal comparisons -- Strategies for developing sets of orthogonal comparisons -- Protection levels for orthogonal comparisons -- Orthogonal polynomials -- Nonorthogonal comparisons -- Summary and recommendations -- 3. Post hoc comparisons: pairwise methods -- Rationale for range tests -- Sampling distribution of ranges -- Tukey's honestly significant difference test (HSD) -- Newman-Keuls test -- Tukey's wholly significant difference test (WSD) -- The Duncan Test -- Lease significant difference test (LSD) -- Pairwise comparisons and Type I error -- Comparisons of pairwise methods -- Dunnett's test -- 4. Post Hoc comparisons: The Scheff(c)♭ Test -- Controls for reducing Type I errors in post hoc comparisons -- Conducting the Scheff(c)♭ test -- Characteristics of the Scheff(c)♭ test -- 5. Multiple comparisons in factorial designs -- Familywise Type I error -- A nonquantitative approach for examining interactions -- Simple Main effects -- Multiple comparisons on interactions -- Range tests and interactions -- Planned comparisons and interaction effects -- 6. Additional considerations -- Unequal sample sizes -- Violations of assumptions -- Concluding remarks